Effect on Intraocular Pressure of Switching from Latanoprost and Travoprost Monotherapy to Timolol Fixed Combinations in Patients with Normal-Tension Glaucoma. (19th November 2014) - Igarashi, Ryoko; Togano, Tetsuya; Sakaue, Yuta; Yoshino, Takaiko; Ueda, Jun; Fukuchi, Takeo
Abstract : Purpose . To evaluate the effect on intraocular pressure (IOP) of switching from latanoprost and travoprost monotherapy to timolol fixed combinations in Japanese patients with normal-tension glaucoma (NTG). Methods . 27 NTG patients (54 eyes) were compared IOP, superficial punctuate keratitis (SPK) scores, and conjunctival injection scores in eyes treated with prostaglandin (PG) or PG analog/beta-blocker (PG/b) fixed-combination 6 months after the change in therapy. Results . The mean baseline intraocular pressure was 17.4 ± 1.59  mmHg in eyes receiving PG therapy only and 17.4 ± 1.69  mmHg in eyes switched to PG/b. Switching to fixed combination therapy from PG monotherapy, the mean IOP was 13.1 ± 1.79  mmHg ( P < 0.001 )   ( - 24.71 % reduction from baseline) at 6 months. The mean conjunctival injection score was 0.69 for eyes on PG monotherapy and 0.56 for eyes on fixed combination therapy ( P = 0.028 ) . The mean SPK scores were 0.46 and 0.53. This difference was not statistically significant ( P = 0.463 ) . Conclusions . Switching from PG monotherapy to PG/b fixed combination therapy for NTG resulted in a greater intraocular pressure reduction than PG alone without increasing the number of instillations.